Annotated checklist and illustrations of Pinnularia species in the Marikina River, Rizal (Luzon), the Philippines - Martinez-Goss, Milagrosa; Ohtsuka, Taisuke; Arguelles, Eldrin DLR.; Ikeya, Tohru; Peralta, Elfritzson M.; Papa, Rey Donne S.; Okuda, Noboru (2025)
A floristic study of the diatoms in the genus Pinnularia Ehrenberg (Bacillariophyceae) was conducted along the Marikina River in the eastern part of Metro Manila, the Philippines. A total of 17 species were identified and described under the bright field light microscope. Habitat descriptions for each Pinnularia species are provided. Notably, 13 out of the 17 species are new records for the country: P. aquaedulcis Liu, Kociolek & Wang, P. borealis var. sublinearis Krammer, P. cf. claasseniae Cholnoky, P. divergens var. mesoleptiformis Krammer & Metzeltin, P. mesoleptiformis Krammer, P. reichardtii Krammer, P. rhombofasciata Krammer & Metzeltin, P. saprophila Lange-Bertalot, Kobayasi & Krammer, P. saprotolerans Lange-Bertalot & Metzeltin, P. subgibba var. undulata Krammer, P. substomatophora Hustedt, P. trivialiformis Lange-Bertalot & Metzeltin, and P. cf. vietnamogibba Kezlya, Y.Maltsev, Krivova & M.Kulikovskiy. This study increases the total number of Pinnularia taxa validly recorded in the Philippines to 56, including from previous studies dating back to 1925.
Keywords: Taxonomy; Habitat (Ecology); Ecosystem; Diatoms